STEREOTIP GENDER PADA PROFESI GURU TARI LAKI-LAKI DI LINGKUNGAN PENDIDIKAN FORMAL - Candra, Ronald; Sekar Sari, Putri; Nuansa, Audrey Govira (Jurnal Studi Gender dan Anak, 2023)
The research departs from the phenomenon of gender stereotypes where male teachers teaching dance education in formal schools are considered uncommon and give the impression of being less masculine. The research aims to find out what gender stereotypes are in the dance arts teaching profession in a formal school environment. In order to approach the research problem, Husserl's phenomenological theory was used. The method used is descriptive qualitative. Data collection techniques and sources through relevant literature studies which are analyzed comprehensively and empirically. The research results concluded that to avoid discrimination against gender stereotypes, there needs to be wider awareness and understanding of gender in society. Apart from that, the role of male dance education teachers in the formal education environment has a big role because it can be a motivation for students that dance education does not affect a man's masculinity if it is carried out professionally and appropriately.